EUROPEAN UNION AND INTERNATIONAL RELATIONS: OLD TIMES, NEW TIMES? - Martins, Marco (PEOPLE: International Journal of Social Sciences, 2018)
Today, Europe is living a new decisive time as it has been in its past after World War II, in search of unity in diversity in the name of a peace project to safeguard future. If, on the one hand, Europe expresses aspirations for profound changes in its external environment, in the domestic context, it ends up colliding with aspects linked to sovereignty and human rights; on the other hand, in European foreign policy, the model reveals the search to legitimize its action. Precisely, the objective and the motivation of this study seek, through the qualitative methodology in Political Science, to analyse and understand the current context of the European Union in the international system. In fact, it is identified that this new hierarchy of powers, in the reaffirmation of the Westphalian system, where economic power comes, is bound to consolidate the democratic development between the old and new times of international relations in the destiny of Europe. From the results obtained during the analysis, in order to face again the unpredictability of the world scenario, it is a reality that Europe must promote the re-encounter of an alternative role, in other words, to assume its initial project of European edification in the name of equality of circumstances and rights of its affirmation in the global arena.